Envy and the Destruction of the Quraysh at Badr - Ouedraogo, Inoussa (Yunus) (Journal of Islamic Sciences, 2025)
Envy is an incurable disease that has ravaged and continues to ravage many countries and institutions. It may begin with a few individuals, then grow and develop until it becomes a national project in disguise. There is no doubt that the Battle of Badr is one of the greatest events in history, and its hidden cause—beyond God’s inevitable decree—was the envy of some spiteful people toward the Prophet (peace and blessings be upon him). So, who among the infidels played this role, and what factors contributed to it? What lessons can we draw from it? This research answers these questions, providing a summary of the Battle of Badr and the decisive moment of its outbreak. The researcher divided the study into five axes. The first axis addresses the definition of envy, its types, and its danger to society. The second axis addresses the conclusion of the Battle of Badr. The third axis explains the decisive moment before the start of the battle at Badr and the role of Abu Jahl in it. The fourth axis explains the role of envy in war and the factors that reinforced it. The fifth and final axis draws social lessons from Badr, followed by the conclusion and results. The researcher adopted a descriptive and analytical approach to collect historical evidence, analyze it, and draw social lessons from it. Among the study’s findings are: Confirmation of the centrality of envy in the emergence of most crises that arise between people. Envy often stems from a single individual and can claim the lives of thousands. Abu Jahl’s hatred found an opportunity to become a national project, resulting in the deaths of many, due to the weak character of the commander-in-chief, Utbah, as well as the fragile leadership of the authorities and regimes. Reckless people always play pivotal roles, leading them to the abyss. The collapse of nations and regimes does not mean a lack of competent leaders, but rather because the scum may accumulate and block their paths. This can be concluded by comparing the personalities of Al-Akhnas ibn Shuraik and Utbah. The former was strong but not a general leader, while the latter was a general leader but weak.